Situation Report: Bulgaria, 15 January 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov to Visit India "Rabotnichesko Delo" Defends Loyalty to the Soviet Union Bulgarian Paper Criticizes Yugoslav Journalist Giant Agricultural-Industrial Complexes Formed Miscellaneous Tano Tsolov Named Head of the Bulgarian Delegation to the 22nd Comecon Session Bulgarian Ambassador Received by Soviet Planning Chief Soviet Minister of Geology in Sofia New Weekly Begins Publication